The Effects of Olive Oil (Olea Europaea L.) on Cathallase Enzyme Levels in White Rats (Rattus Norvegicus) Wistar Strain of Obese Male - Salmalia, Raisya Zahra; Gayatri, Sri Wahyuni; Zulfahmidah, Zulfahmidah; Syamsu, Rachmat Faisal; Rasfayanah, Rasfayanah (PT FORMOSA CENDEKIA GLOBAL, 2024)
Obesity is a condition of the body resulting from excessive fat accumulation which leads to health problems. The increase in fat metabolism affects increased production of free radicals in the circulation and in adipocyte cells. Free radicals that increase in the body are not in line with antioxidant enzymes, causing a condition called oxidative stress. The body's defense mechanism against free radicals is the synthesis of antioxidants. When there is a decrease in the activity of endogenous antioxidants such as the catalase enzyme, it provides a strong indication of oxidative stress. The presence of polyphenols and monounsaturated fatty acids in olive oil is useful for preventing chronic damage that causes oxidative stress. The catalase enzyme can be used as a parameter for an uncontrolled increase in ROS (Reactive Oxygen Species) or disruption of the function of the antioxidant defense system. To determine changes in levels of the catalase enzyme in an obese male Wistar strain white rat (Rattus norvegicus) animal model that was given olive oil. This research used a true experimental laboratory with a pre- post test design. The results of the study were significant changes in catalase enzyme levels in the olive oil intervention group (p-value 0.003<0.05) on day 14 and day 28 with (p-value 0.002<0.05 and 0.005<0.05). In the group given olive oil, the effect on the level of catalase enzyme was most significant on day 28 (p-value 0.002<0.05).